Cryogenic Performance Test Platform for the Gas Bearings of Helium Turbine Expanders. Issue 1 (March 2020) - Li, S S; Fu, B; Zhang, Q Y; Zhu, P; Lu, X F; Ma, D K; Yuan, K
Abstract: The turbo-expander is the core part of the helium refrigerator, and the gas bearing is the critical component influences the stability of the machine. There is 300 K operating temperature difference between the turbine wheel and the gas bearing regions in the helium turbo-expander. Therefore, it is necessary to consider the heat transfer between the bearing surfaces, nominally at room temperature, and the rest of the machine when studying bearing dynamic stability. This paper describes a cryogenic test platform that is being developed to analyze the dynamic performance of gas bearings with cryogenic gas supply. The system flow loop has been designed for bearing and small turbine testing at 80 K and above. The experimental method has been determined. All of the components are ready for the cold box assembly. The commissioning of the platform will be carried out in the near future.